The Effect of Perceived Risk in Online Shopping Intention: Does Attitude Mediate the Relationship? - K.M. MAKHITHA; K.M. NGOBENI (Expert Journal of Marketing, 2024)
Engagement in online shopping by specific emerging-market consumers in South Africa has been on the rise. Nevertheless, the online usage rate remains low. Online retailers need to understand the perceived risk factors influencing consumers’ attitudes and intention in relation to online shopping for clothing products, especially in South Africa, where online risk is an issue that discourages consumers from making purchases and where the practice of online shopping is still in its infancy. To that end, an online survey was conducted among emerging-market consumers in Soweto, with 300 respondents being targeted and reached. Convenience sampling was adopted to collect data from the respondents. An independent research company collected data, and various statistical analyses such as descriptive analyses, exploratory factor analysis, and structural equation modelling were conducted. The findings revealed that perceived financial, convenience and security risks significantly influenced emerging-market consumers’ attitudes towards online shopping. None of the perceived risks were found to influence consumers’ intention to shop online. The perceived financial, convenience and security risks were found to be mediated by attitude. The study contributes to the body of knowledge about how risk affects consumers' attitudes and intentions to purchase online from a developing nation’s viewpoint and for a particular product category. The study also contributes to existing knowledge on the mediation effect attitude has on the relationship between perceived risk and intention to shop online. The findings are also valuable for online retailers seeking to direct their offerings at emerging-market consumers and could potentially be incorporated into their online retail and marketing strategies.